Práticas autorais do cordel no contexto da propriedade intelectual - Maia, Manuela Eugênio (2018)
The Cordel is an unexplored theme in the ambit of thesis produced along with the PostGraduation into Information Science in Brazil. From the 17(seventeen) programs identified by the Brazilian Association of Education in Information Science (2014) and, correlated with data obtained in the Digital Library of Thesis and Dissertations, there is a potential field for researches that approach this literary genre in the context of the area. It makes possible to the researcher a plurality of analysis, which can be performed. Towards this, one of the themes that stood out in this spectrum was regarding the authorship, mainly, concerning the provision of digital content in the base developed in the ambit of this Library, which has been worked for more than a decade in this universe, commenced in 2006 by the managing of the Library of Rare Artworks Átila Almeida. By addressing the cordel, the reframed northeastern literary phenomenon, a descriptive complexity was noticed and, concerning the intellectual producer, controversies regarding the role of the owner and author-owner. Researching on this distinction between author and owner in a diachronic way involves the perception of the cordelistas about the mechanisms, which involve the intellectual property and its legalist scope today. Problem: How are characterized and how are performed the copyright practices of the cordel in the context of the intellectual property? Therefore, the general objective of this study is to analyse the authorship practices of the cordel in the context of the intellectual property. In this direction, the thesis lays on the proof of the following statement: the authorship in the cordel is characterized by three perspectives – the uniqueness, the plagiarism and the intertextuality, when the document pervades the process of authorial reframing. This research involves a perspective of multiplicity of meanings, anchoring on the hermeneutic as mechanism of interpretation, including the subject in its symbolic, cultural and procedural universe. The research is quantitative and qualitative, assuming documental, bibliographic and descriptive characteristics, using the following data collection instruments: (a) interview with cordelistas and related personalities, (b) 1,044 digitalized cordéis from the acquis of the Library of Rare Artworks Átila Almeida and (c) list with 13,296 pamphlets of the mentioned library. It is proved in the social, cultural and commercial fields the limits of the complex relations, which involve the cordel in the areas of the authorship practices and of the intellectual copyright.